PENGARUH CELEBRITY ENDORSEMENT, CITRA MEREK, KEPERCAYAAN MEREK DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK EIGER DI PURWOKERTO - Nuha, Muhammad Aufa Abyan; Astuti, Herni Justiana; Miftahuddin, Muchammad Agung (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This study aims to analyze the effect of celebrity endorsement, brand image, brand trust and lifestyle on purchasing decisions for Eiger products in Purwokerto. This type of research includes quantitative research with a research sample of 100 respondents who live in Purwokerto. The sampling method used was purposive sampling by distributing questionnaires, which involved selecting respondents who were willing and met the specified sample criteria. Data analysis used by the structural equation modeling method with the Smart PLS Version 4.0 tool. There are two tests carried out, namely the structural model or inner model and the measurement model or outer model and hypothesis testing is carried out to test the significance of the influence of each independent variable on the dependent variable. The results showed that celebrity endorsement, brand trust and lifestyle have a significant effect on purchasing decisions for Eiger products. Brand image shows no significant effect on purchasing decisions for Eiger products. Keywords : Celebrity Endorsement; Brand Image; Brand Trust; Lifestyle